Effects of α-Particle Radiation on DNA Methylation in Human Hepatocytes - Xiangming Xue; Lixia Su; Teng Zhang; Jingming Zhan; Xiaona Gu (SAGE Publishing, 2024)
Objective: This paper explores the role of DNA methylation in α-irradiation damage at the cellular level. Methods: Human normal hepatocytes L-02 were irradiated using a 241 Am α source at doses of 0, 1.0, and 2.0 Gy. The methylation levels of the six differentially methylated genes were examined by pyrophosphate sequencing, and the mRNA expression levels of the six differentially methylated genes were examined by real-time fluorescence quantitative PCR. Results: The rate of γH2AX foci positive cells was significantly higher than that of the control group after irradiation of cells in different dose groups for 1 h and 2 h respectively ( P < .05). The proportion of S-phase cells was significantly increased in the 1.0 Gy and 2.0 Gy dose groups compared with the control group ( P < .05). The methylation levels of CDK2AP1, PDGFRL, PCDHB16 and FAS genes were significantly increased, while the mRNA expression levels were significantly decreased ( P < .05). The expression levels of CDK2Apl, PCDHB16 and FAS were significantly negatively correlated with the methylation levels ( P < .05). Conclusion: The α-particle radiation can affect gene expression at the epigenetic level, which led to the speculation that altered methylation levels of CDK2AP1, PCDHB16, and FAS genes may be involved in the α radiation damage process.